ANALISIS KEBERLANJUTAN PROGRAM KTB (KAMPUNG TANGGUH BENCANA) DALAM MENGHADAPI BENCANA DI KEMANTREN JETIS DAN KEMANTREN UMBULHARJO KOTA YOGYAKARTA - Elizabhet Ortarita Minto Ariwati; Arif Rianto Budi Nugroho; Eko Teguh Paripurno; Johan Danu Prasetya; Yohana Noradika Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Indonesia is a disaster-prone country that requires strengthening community capacity as a key strategy for disaster risk reduction. The Disaster Resilient Village Program (Kampung Tangguh Bencana – KTB) was developed as a community-based disaster management initiative to enhance preparedness, program sustainability, and community self-reliance. This study aimed to analyze the level of community participation, program sustainability, and community independence in the implementation of the KTB Program in Jetis and Umbulharjo Subdistricts, Yogyakarta City. A mixed-methods approach was employed, combining quantitative and qualitative methods. Quantitative data were collected through questionnaires administered to 761 respondents and analyzed using a Likert scale, while qualitative data were obtained through in-depth interviews, participatory observation, and documentation involving officials from the Regional Disaster Management Agency (BPBD), disaster management facilitators, KTB leaders and members, volunteer communities, and non-KTB residents. The results indicate that community participation in both subdistricts was high and corresponded to the partnership level of participation based on Arnstein’s ladder. The sustainability analysis revealed that all KTBs were categorized as sustainable to self-reliant, with mean scores ranging from 4.20 to 4.33, and none were classified as vulnerable. Several villages namely Badran, Penumping, Tahunan, and Tempel Wirogunan demonstrated higher levels of self-reliance, supported by routine activities, innovative local funding mechanisms, and well-developed organizational capacity. Nevertheless, challenges remain, particularly related to leadership regeneration, fluctuations in community participation during non-disaster periods, and technical dependence on BPBD for large-scale activities. This study highlights the importance of strengthening institutional capacity and providing continuous facilitation to ensure the long-term and equitable self-reliance of Disaster Resilient Villages.